Sequential fractionation and characterization of lignin and cellulose fiber from waste rice bran. Issue 5 (October 2020) - Arun, Varun; Perumal, Eashwar M.; Prakash, Kandheish Arul; Rajesh, Mathur; Tamilarasan, Krishnamurthi
Graphical abstract: Highlights: Fractionation of lignin from rice bran using acid pre-treatment process. Extraction of cellulose fibers from rice bran using alkali bleaching process. Characterization of lignin fraction by UV, FTIR, and MALDI-TOF-MS analysis· Changes of biomass surface analysis by SEM, XRD, FTIR and XPS. Abstract: Cellulose and lignin were simultaneously isolated from rice bran is an interesting and alternative renewable materials synthesis for industrial application. In the present research, acid pre-treatment (AT) (85 % organic acid, 80 °C, 120 min) has been proposed for the fractionation of lignin from rice bran (RB). After end of the pre-treatment, residual RB was further submitted to bleaching treatment (BT) (1.7 % sodium chlorite, 60 °C, 120 min) for fractionation of cellulose fibres. The isolated lignin structure was extensively characterized using UV–vis spectroscopy, Fourier-transform infrared spectroscopy (FT-IR) and matrix assisted laser desorption/ionisation-time of flight-mass spectrometry (MALDI-TOF-MS). In addition, surface morphology and surface elemental composition of untreated rice bran (UT-RB), acid treated rice bran (AT-RB) and bleaching treatment rice bran (BT-RB) were performed by X-ray photoelectron spectroscopy (XPS), SEM, XRD and FTIR. Fractionated lignin and cellulose fibres could be used as feedstock in the integrated biorefineries application.